Apple pomace-based rations for White Leghorn pullets - BHAT, G A; KHAN, A A; BANDAY, M T (The Indian Journal of Animal Sciences, 2012)
A study was conducted on 315 layer type birds to evaluate the effect of feeding apple pomace-based diets with or without enzyme supplementation (each gram of multi-enzyme mixture contained amylase 2400, hemi-cellulase 5400, cellulose 12000, protease 2400 and α-glucanase 160 units respectively) on their performance from 21–34 weeks of age. Egg type birds (315) at 8 weeks of age were distributed into 7 treatment groups each group having 3 replicates with 15 birds in each and reared in deep litter system of housing. While T1 acted as a control and was offered basal diet, remaining groups were offered diets where in maize was replaced by apple pomace to the extent of 10% in T2 and T3, 15% in T4 and T5, and 20% in T6 and T7. Diets offered to the groups T2, T4 and T6 were supplemented with multi- enzyme mixture @ 1g/kg feed. The results indicated no significant difference in the age at sexual maturity through numerically it was lowest for the control and increased with corresponding increase in the level of apple pomace. Age at 25 and 50% production was higher in groups offered apple-pomace based diets. However, the increase was statistically significant for 25% egg production in T3 group and for 50% egg production in T5 group as compared to control.Overall egg production was lower in the groups fed diets in which AP replaced 20% of maize either with or without enzyme supplementation while the groups offered diets with 10% replacement of maize with AP with or without enzyme supplementation and 15% replacement with enzyme supplementation had egg production which was statistically non- significant from control. Accordingly FCR both in terms of feed consumed/kg egg mass and feed consumed per dozen eggs was significantly higher (adverse) in groups with 20% replacement as well as 15% replacement without enzyme supplementation while as in groups with 10% replacement with or without enzyme supplementation and 15% replacement with enzyme supplementation, the FCR did not differ significantly from control. No significant difference between the groups was realized with respect to egg weight and mortality. Replacement of maize by apple pomace to the extent of 10% without enzyme supplementation and 15% with enzyme supplementation did not have any adverse effect on age of sexual majority and egg production from 21–34 weeks of age.